Blood culture findings as tools for clinical management and patient safety - Costa, Josiane Moreira da; Malta, Jessica Soares; Oliveira Ortiz, Mayara; Aparecida de Sousa, Denise; Magalhães, Aline de Cássia; Silva, Augusto César da; Queiroz Ribeiro, Andréia; Braga, Lucas de Faria Martins; Pinheiro Cintra, Leandro; Pádua, Cristiane Aparecida Menezes de (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Healthcare-associated Infections (HAI) have a significant impact on public health, and the use of indicators is a common practice for assessing and improving healthcare services. Aim: This study aimed to describe the utilization of blood culture results to develop indicators for hospital management and evaluate antimicrobial resistance. Outlining: This cross-sectional study was conducted at a teaching hospital. Blood cultures were performed during two periods: pre-implementation of antimicrobial sales restrictions in Brazil (05/2010-10/2010 - first period) and post-implementation (02/2011-07/2011 - second period). Computerized system reports were used to develop indicators, including infection incidence rates and antimicrobial resistance. Results: A higher infection rate (1.97/100 person-days) and a lower resistance rate (0.62/100 person-days) were observed in the second period, with the microorganism Staphylococcus sp. being more frequently identified in both periods. Implications: This study demonstrates the use of indicators to evaluate governmental actions related to HAIs, which can contribute to patient safety and healthcare management.